Biological Aspects and Feeding Habits of Spinetail Devil Ray (Mobula mobular) landed in the Palabuhanratu Nusantara Fishing Port - Fahira Anggi Novyanti; Selvia Oktaviyani; Moch. Rudyansyah Ismail; Yuniarti M.S.; Alexander M.A Khan (Jurnal Kelautan Tropis, 2023)
Optimal management of aquatic resources requires a good understanding of the biological aspects and other information related to these resources. This study was conducted to determine the biological aspects and feeding habits of Mobula mobular landed in the Palabuhanratu Nusantara Fishing Port. The research was conducted from September 2021 to May 2022. Data collected through a direct survey that included aspects of biology, stomach contents and information on fishing grounds. It was recorded that 21 individuals of M. mobular landed in the area during the study period. According to the Chi-Square test, the sex ratio between females and males is balanced with the growth pattern of M. mobular was negatively allometric. The male of M. mobular was generally found as immature individuals. The prey items identified in the stomachs belong to five groups: decapods, copepods, gastropods, Polychaeta, and others. Decapods were the most important prey (Index of Relative Importance 99,54%), while the other prey groups were only as complementary food. M. mobular is categorized as a plankton feeder. The fullness index value was 23.8%, while the vacuity index was 76.2% and categorized as relatively low fed. M. mobular is classified as an omnivorous animal that tends to be carnivorous with an animal preference with a trophic value of level 3.